Astaxanthin: A Compound in the Prevention of Chronic Diseases and as a Potential Adjuvant Treatment Agent - Xiao Zhu; Xi Chen; Matthew Wang; Honghua Hu (Antioxidants)
Astaxanthin (AST) is a fat-soluble carotenoid antioxidant. AST exhibits multiple protective mechanisms, including its antioxidant, anti-inflammatory, immunomodulatory, anti-apoptotic, nervous system-protective, anti-tumor, and anti-fibrotic effects. These effects make it a promising compound for the prevention of chronic diseases. AST can protect the nervous system against neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease. It also protects the liver and helps reduce the risk of chronic kidney disease. Additionally, it improves cardiovascular health and has anti-diabetic properties. This review aims to provide an updated overview covering the protective effects of AST against various chronic diseases, including its antioxidant, anti-inflammatory, and anti-apoptotic effects. We also discuss the strategies used for improving astaxanthin bioavailability and its potential as an adjuvant therapeutic agent.